Timestalker [videorecording (DVD)] - Lowe, Alice, 1977-; Lowe, Alice, 1977-; Anderson, Jacob, 1990-; Barnard, Aneurin, 1987-; Reynolds, Tanya, 1991- (Level 33 Entertainment, 2025)
Agnes, a hapless heroine, falls for a mysterious man, promptly meets her bloody demise, and then is reincarnated a century later. When she meets her love again, the cycle begins anew. As Agnes traverses through time, she repeats all the messy thrills and spills that come with daring to follow one's heart. How can she ever hope to break the cycle when she's destined to be a fool for love?